The human transient receptor potential vanilloid 3 channel is sensitized via the ERK pathway - Vyklicka, Lenka; Boukalova, Stepana; Macikova, Lucie; Chvojka, Stepan; Vlachova, Viktorie (The Journal of biological chemistry, 2017)
The transient receptor potential vanilloid 3 (TRPV3) channel is a Ca2+-permeable thermosensitive ion channel widely expressed in keratinocytes, where together with epidermal growth factor receptor (EGFR) forms a signaling complex regulating epidermal homeostasis. Proper signaling through this complex is achieved and maintained via several pathways in which TRPV3 activation is absolutely required. Results of recent studies have suggested that low-level constitutive activity of TRPV3 induces EGFR-dependent signaling that, in turn, amplifies TRPV3 via activation of the mitogen-activated protein kinase ERK in a positive feedback loop. Here, we explored the molecular mechanism that increases TRPV3 activity through EGFR activation. We used mutagenesis and whole-cell patch clamp experiments on TRPV3 channels endogenously expressed in an immortalized human keratinocyte cell line (HaCaT) and in transiently transfected HEK293T cells and found that the sensitizing effect of EGFR on TRPV3 is mediated by ERK. We observed that ERK-mediated phosphorylation of TRPV3 alters its responsiveness to repeated chemical stimuli. Among several putative ERK phosphorylation sites, we identified threonine 264 in the N-terminal ankyrin repeat domain as the most critical site for the ERK-dependent modulation of TRPV3 channel activity. Of note, Thr264 is in close vicinity to a structurally and functionally important TRPV3 region comprising an atypical finger 3 and oxygen-dependent hydroxylation site. In summary, our findings indicate that Thr264 in TRPV3 is a key ERK phosphorylation site mediating EGFR-induced sensitization of the channel to stimulate signaling pathways involved in regulating skin homeostasis.
Keywords: modulátory membránového transportu; TRPV Cation Channels; Cell Line, Transformed; Patch-Clamp Techniques; transformované buněčné linie; Recombinant Proteins; ankyrin repeat domain; mutace; interakční proteinové domény a motivy; Up-Regulation; HEK293 buňky; posttranslační úpravy proteinů; cymeny; TRP channels; fosforylace; Mitogen-Activated Protein Kinase 3; Phosphorylation; keratinocyte; mutageneze cílená; upregulace; HEK293 Cells; epidermal growth factor receptor (EGFR); monoterpeny; metoda terčíkového zámku; Epidermal Growth Factor; Protein Processing, Post-Translational; Keratinocytes; Monoterpenes; MAP kinasový signální systém; extracellular-signal-regulated kinase (ERK); Protein Interaction Domains and Motifs; rekombinantní proteiny; MAP Kinase Signaling System; Mutagenesis, Site-Directed; zelené fluorescenční proteiny; keratinocyty; phosphorylation; lidé; transient receptor potential channels (TRP channels); Humans; mitogenem aktivovaná proteinkinasa 3; Cymenes; Green Fluorescent Proteins; threonin; Mutation; sloučeniny boru; Boron Compounds; Threonine; kationtové kanály TRPV; ErbB Receptors; erbB receptory; Membrane Transport Modulators; epidermální růstový faktor